Existence of weak solutions for the incompressible Euler equations - Wiedemann, Emil (Annales de l'Institut Henri Poincaré - Analyse Non Linéaire, 2011)
Using a recent result of C. De Lellis and L. Székelyhidi Jr. (2010) [2] we show that, in the case of periodic boundary conditions and for arbitrary space dimension d≥2, there exist infinitely many global weak solutions to the incompressible Euler equations with initial data v0, where v0 may be any solenoidal L2-vectorfield. In addition, the energy of these solutions is bounded in time.© 2011 Elsevier Masson SAS. All rights reserved.
CRIS-Team Scopus Importer:2023-01-17